Labor after cesarean delivery managed without induction or augmentation of labor. Issue 4 (2nd May 2017) - Nakamura, Kohei; Hayashi, Shusaku; Sasahara, Jun; Okamoto, Yoko; Ishii, Keisuke; Mitsuda, Nobuaki
Abstract: Background: This study aimed to describe the perinatal outcomes of women opting for vaginal birth after cesarean delivery (VBAC) managed without induction or augmentation of labor. Methods: This was a retrospective cohort study of candidates for VBAC at a tertiary center in Japan from April 2003 to March 2012. Women with singleton gestations and one prior low‐transverse cesarean delivery who intended VBAC at 36 weeks of gestation were identified as candidates for VBAC and included in the study. Participants were managed without induction or augmentation of labor. Maternal characteristics and perinatal outcomes were obtained from medical records. Factors associated with successful VBAC were analyzed with a multivariable logistic regression model. Results: Of 333 candidates for VBAC, 242 (72.7%) had vaginal birth, 49 (14.7%) had repeat cesarean delivery with spontaneous labor, and 42 (12.6%) had repeat cesarean delivery without spontaneous labor. The rate of uterine rupture was 0.3% (1/333). Prior vaginal delivery and nonrecurring indications for prior cesarean delivery were associated with successful VBAC. Conclusions: Management of candidates for VBAC without induction or augmentation of labor resulted in a high VBAC rate and favorable perinatal outcomes. Such restrictive VBAC policies may be an acceptable alternative to standard management or abandonment of VBAC.